Watermelon (Citrullus lanatus) Rind Extract-Mediated Synthesis of Manganese (II, III) Oxide Nanoparticles for Potential Theranostic Applications - Zaragosa, Gelo P.; D. Ilem, Carlo Nonato; Garcia, Joel (Applied Science and Engineering Progress, 2024)
Plant extracts and microorganisms are widely utilized for the green synthesis of Mn3O4 nanoparticles. In this study, green synthesis of Mn3O4 nanoparticles for theranostic applications was performed using watermelon (Citrullus lanatus) rind extract as a reducing and stabilizing agent. The UV-visible absorption of the nanoparticles at 196 nm is associated with the surface plasmon resonance of Mn3O4 nanoparticles. FT-IR spectra presented the key chemical functional groups associated with the Mn–O vibrations and phytoconstituents of the watermelon rind extract. XRD analysis revealed the single-phase hausmannite crystalline structure of the Mn3O4 nanoparticles with an average crystallite size of 35.2 nm. SEM and TEM images of the synthesized Mn3O4 nanoparticles showed quasi-spherical shapes and a core size of 52.90 ± 8.19 nm and 35.89 ± 0.83 nm, respectively. EDS analysis indicated that the nanoparticles mainly comprised Mn, O, and C. Furthermore, the radical scavenging activity through the DPPH assay showed that the nanoparticles have significant antioxidant therapeutic potential, with an IC50 value of 20.62 ± 0.69 ppm. T1 and T2 relaxivities of Mn3O4 nanoparticles were 5.34 ± 0.11 mM–1s–1 and 63.47 ± 0.60 mM–1s–1, respectively, when measured at a clinically relevant field strength of 1.5 T, confirming their suitability as an MRI contrast agent for diagnostic imaging. These findings imply that the green synthesized Mn3O4 nanoparticles could be used as a theranostic agent for MRI applications.